Determination of Tolerances of Some Flax Varieties to Different Doses of Salt Concentrations in Early Development Period - Yaşar, Mustafa; Yetişsin, Fuat (Institute of Economic Development and Social Researches, 2023)
It is widely accepted that soil salinity increases over time and is triggered by the effect of climate change. The aim of this research is to examine the germination, growth response and tolerance of some flax (Linum usitatissimum L.) varieties of different salinity levels. This study was carried out with 11 flax genotypes in 2022 in the germination laboratory of Muş Alparslan University, Faculty of Applied Sciences, Plant Production and Technologies. The research was established according to the Randomized Plots Trial Design with 4 replications, and 0, 75, 150 and 225 mM NaCl salt solution levels were applied. In the analysis of variance, genotype, salt levels and genotype*salt level interaction were found to be statistically significant at the P <0.01 level in terms of all the traits examined. In all cultivars used in the study, 75 mM NaCl concentration showed a positive stimulating effect on germination. However, although 150 mM NaCl concentration had a germination-promoting effect, it negatively affected normal seedling formation. As a result, when the anatomical, physiological and biochemical findings of flax varieties are evaluated as a whole in the early development period; It was determined that the most sensitive cultivars to salinity were G2, G10, and G11 varieties, moderately sensitive varieties were G1, G4, G5 and G8, in terms of all doses, the most stable variety was G3, in addition G6, G7 and G9 of varieties showed good results in terms of all traits. However, it was concluded that these varieties should be cultivated under field conditions in order to obtain more decisive results. © 2023, Institute of Economic Development and Social Researches. All rights reserved.
Keywords: Correlation; Flax; Germination Seed; Mda; Nacl; Proline; Tolererence